Clinical observation of VR virtual reality rehabilitation training combined with acupuncture in the treatment of mild cognitive impairment - Ying Fu; Hui Wang (SLAS Technology)
Mild cognitive impairment (MCI) is an intermediate state between normal aging and dementia, and its symptoms include easy forgetting, distraction, and mental deterioration. This directly affects the patient's motor function, daily living ability, and social adaptability, and brings many difficulties to the patient's reintegration into society. Therefore, clinical research on MCI is very necessary. The purpose of this paper is to study the efficacy of acupuncture and moxibustion in the treatment of MCI based on VR virtual reality technology. This paper firstly expounds the application prospect of VR virtual reality rehabilitation training and virtual scene intervention in MCI patients. It then introduces the characteristics of acupuncture and the acupuncture points of scalp acupuncture and eye acupuncture. This paper then establishes the algorithm model of the VR virtual reality rehabilitation training system, which lays a solid foundation for the design of the subsequent rehabilitation training system. This paper then conducts clinical experiments and analysis on the treatment of mild cognitive impairment, which establishes a treatment group and a control group for comparative experiments. The experimental results showed that the combined effect size OR = 2.74 of the meta-analysis, the combined effect size test statistic Z = 3.38, WMD = 2.42, and the 95 % CI was (1.98, 3.06). It indicated that the treatment group had better efficacy. The MMSE score and MoCA score of the treatment group after treatment and training increased by 28.68 % and 15.36 %, respectively, and the scores were higher than those of the control group. Therefore, the use of VR virtual reality technology combined with acupuncture is of great significance for the rehabilitation and treatment of patients with mild cognitive impairment.